Compressive Strength Characteristics of Trass Stabilized Dredged Soil - Komang Arya Utama; Tri Harianto; Achmad Bakri Muhiddin; Ardy Arsyad (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2022)
Landslides from Mount Bawakaraeng caldera in 2004 has caused high dam sedimentation at the lower reaches of the Jeneberang River. The availability of this large sedimentary material makes this material need to be considered as an alternative to new materials in the geotechnical field. However, the results of laboratory tests applied to sedimentary materials show that the mechanical characteristics of these materials are not sufficient for construction materials. Therefore, it is very important to conduct a study on how to improve the quality of dredged soil by adding Trass as stabilizing agent to improve the quality of the mechanical properties of the dredged soil. This study aims to analyze the mechanical characteristics of the dredged soil stabilized with Trass. The research was conducted by adding Trass with composition 3%; 6%; 9% and 12%; respectively to the dry weight of the dredged soil. The curing time was applied for a period of 3, 7 and 14 days to analyze the significant binding of Trass to the stabilized dredged soil. Laboratory tests was conducted to the density test and unconfined compression test. The results showed that there was an increase in the maximum dry density of the dredged soil between 1.41% - 3.56% due to the addition of trass, and a decrease in the optimum water content between 0.8% - 2.7%. In addition, there was an increase in the value of free compressive strength from 47.76% to 388.89% in the trass stabilized dredged soil during the curing period of 3, 7 and 14 days. The use of dredged soil and trass as stabilizing agent can be an alternative option in soil improvement efforts based on the utilization of waste material and local content potential.